LA INDUMENTARIA TRADICIONAL FEMENINA A TRAVÉS DEL BELÉN DE SALZILLO: LA MATANZA DE LOS INOCENTES - Gómez de Rueda, Isabel (Imafronte, 1999)
The 18th century as alwais been a point of reference for what we now know as traditional costume. This consists of items of clothing which have followed a traditional and eskewed the whims of foreign fashions. They have been worn by ordinary people. These garments originated from different historical periods and were also subject to differene influences. They. reached Murcia through diver se chanels. The discovery of these items of clothing provides an extremely important historical documental of 18th century society and its context. No-one has more vividily captured this than the famous Murcian sculptor Francisco Salzillo ti his crib, and his follower Roque López. They both have shown what the haroqueladi’ of the period was like and whar she wore.